STUDY OF NORMAL ANATOMICAL VARIATIONS IN PARA-NASAL SINUSES USING COMPUTED TOMOGRAPHY SCAN: A CROSS SECTIONAL STUDY FROM CENTRAL INDIA - Patil, Sunil; Shendey, Shweta; Ansari, Ibrahim (Journal of Biomedical and Pharmaceutical Research, 2019)
Background: The standard imaging in the assessment of the para-nasal sinuses is currently computed tomography scanning. This provides an applied anatomical view of the area as well as the common anatomical variants. The advancement and improvement of computed tomography scans has provided for a comprehensive evaluation of patients' para-nasal sinuses, allowing Functional Endoscopic Sinus Surgery surgeons to operate with a guide chart.Objectives: To study normal anatomical variations in para-nasal sinuses using Computed Tomography.Material and Methods: This research took place in a tertiary healthcare center's radiology department over the course of two years. Axial para-nasal sinuses cuts were taken using a multi-slice (128 slice scanner), followed by coronal and sagittal reconstruction.Results: The most common anatomic variation, according to the findings, was nasal septal deviation. The rarest variation in our sample was Haller cell and pneumatized septum. There was also a close connection between unilateral Concha bullosa and contra-lateral septal deviation, as evidenced by the research.Conclusion: A wide range of lesions can affect the para-nasal sinus area. Normal anatomical differences and congenital abnormalities in this area are significant because they can have pathological consequences or cause difficulty/complication during surgery.Keywords: Para-nasal sinuses, Computed Tomography, Functional Endoscopic Sinus Surgery.